Sosialisasi Tentang Pentingnya Memahami Dinamika Pelayanan Pernikahan Bagi Jemaat Urban di GKSI Hepzhibah Tangerang - Malik Bambangan; Stenly R. Paparang (Jurnal DIKMAS, 2023)
This study aims to find out the method of service of servants of God in the Indonesian Faithful Christian Church (GKSI) Hepzhibah Tangerang congregation in serving urban congregations for the blessing of marriage in the church. Pros and cons began to emerge about this service method. Is this in accordance with church rules and the Bible? Through this study, the researcher will explain the steps taken by GKSI Hepzhibah's servants of God in handling this ministry. The result is that the ministry is still within reasonable limits without violating the principles of the Bible or the GKSI Articles of Association or Bylaws. All members who have received this service feel joyful to be served by the church. They are no longer abandoned like sheep without a shepherd. They also actively attended Sunday worship after they received the marriage blessing service and became active members of GKSI Hepzhibah.